Incidence and outcomes of systemic infections in patients with leadless pacemakers: Data from the Micra IDE study. Issue 8 (2nd July 2019) - El‐Chami, Mikhael F.; Soejima, Kyoko; Piccini, Jonathan P.; Reynolds, Dwight; Ritter, Philippe; Okabe, Toshimasa; Friedman, Paul A.; Cha, Yong‐Mei; Stromberg, Kurt; Holbrook, Reece; Fagan, Dedra H.; Roberts, Paul R.
Abstract: Background: The Micra clinical trials have enrolled more than 2500 patients without any reported device‐related infections that required removal during follow‐up. Leadless pacemakers might be more resistant to bacterial seeding due to smaller surface area and a greater tendency for encapsulation. Objective: To analyze the incidence and outcomes of serious infectious events (SIEs: bacteremia or endocarditis) that developed during follow‐up in patients with history of Micra leadless pacemaker implantation. Methods: SIE and outcomes were characterized based upon adverse event reports. Among 720 patients implanted with Micra in the investigational device exemption trial, we identified 16 patients who had documented 21 SIEs during follow‐up. Results: Among patients with SIEs, mean age was 71.9 ± 11.7 years. SIEs occurred at a mean 4.8 ± 4.5 months after implant and patients were followed for 13.1 ± 9.1 months after documentation of SIE. All events were adjudicated as unrelated to the Micra device or procedure. Bacteremia was documented to be related to a gram‐positive organism in 13 events (seven Staphylococcus, three Streptococcus, two Enterococcus, and one uncharacterized gram‐positive bacteria), and gram‐negative organisms in three events. In five events, the type of organism was not characterized (two patients with endocarditis). No persistent cases of bacteremia after antibiotic cessation were seen over the duration of follow‐up Conclusion: In this small series of Micra patients who developed SIEs postimplant, the occurrence of bacteremia and/or endocarditis did not appear to lead to persistent bacteremia off antibiotics; most events resolved with antibiotic treatment.